RESEARCH ON VIBRATION FEATURE EXTRACTION METHOD OF RAIL TRANSIT VEHICLE SUBGRADE BASED ON WAVELET PACKET Teager DISPERSION ENTROPY - ZHANG Min; SUN LongYin; XIA Tuo; ZHANG Xiong (Jixie qiangdu)
The hoisting and transfer of electrical equipments such as transformers are weak links that are neglected in monitoring,and secondary damage caused by mechanical impact is very easy to occur.The impact response of transformer rail transit vehicle caused by subgrade vibration was studied.Firstly,the rail transit vehicle transformer coupling analysis model was established,and the response area of the rail transit vehicle transformer coupling analysis model under the action of subgrade vibration was obtained by finite element analysis.Then,a non⁃periodic transient response feature extraction method based on wavelet dispersion entropy was proposed.This method performed good sparsity segmentation of the whole frequency band through the optimal subband tree structure of wavelet packet,decomposed the one⁃dimensional data containing a variety of information into different dimensions,and realized the effective decomposition of signals.The impact characteristics of subband signals were enhanced by Teager energy operator(TEO),and the subband signals with impact response characteristics were selected by dispersion entropy.Finally,through the subgrade vibration simulation signal,it is verified that the proposed method can accurately extract the aperiodic transient impact response components from the coupling path interference.